Time to bring about innovation - Abd Razak, Dzulkifli (2008)
TODAY, Universiti Sains Malaysia will make history. It will witness yet another milestone in moving its research and development to the next level in tandem with its newfound status as Malaysia's research university. Much has been said about the need to commercialise the R&D outcome from universities, but in reality this is easier said than done given a host of other interrelated factors that must be in place before one can hope to see a good success story. Generally, the overall success rate of commercialisation is less than 10 per cent. Currently, in Malaysia, it is about half of that. One of the reasons for this is not the lack of quality R&D carried out at the universities. Rather, it has something to do with the culture of risktaking among investors, especially the local ones.